DAYA TARIK WISATA DAN MINAT WISATAWAN TERHADAP PANTAI PARANGTRITIS - , VANI KUSWANDANI, Erlin Estiana Yuanti, S.S., M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One of the beach tourism in Bantul is Parangtritis Beach that has beautiful scenery and many tourists. The number of visitors who came to Parangtritis Beach could be influenced by service factor, infrastructure factor, object and tourist attraction, and safety factor. Therefore, this graduating paper aims to know about tourist attractions and tourist interests on Parangtritis Beach. For collecting data of this research, writer uses 2 (two) methods, there are library research and field research. In library research, writer reads several books from Culture and Tourism Affairs, and articles from the internet which are related to the object of this research. In field research, writer observes to the research object (Parangtritis Beach), and interviews member of staff in Tourism Board on Promotion and Partnership division and Infrastructure Tourist Attraction division. Besides, writer also asks the tourist to fill the questionnaire. From the questionnaire and observation, writer knows and analyses tourist attractions and tourist interests on Parangtritis Beach. Overall, as one of beach tourism in Bantul Regency, Parangtritis Beach has strong tourist attractions an tourist interest such as: scenery (41%), location (26%), facilities (20%), and attraction (13%)